FAKTOR-FAKTOR YANG MEMPENGARUHI PERNIKAHAN USIA DINI DI KELURAHAN SIDODAMAI KECAMATAN SAMARINDA ILIR - Miladya Miladya (ADMINISTRASI PUBLIK, 2020)
It is natural that two people of different sexes, namely a man and a woman, have the power to attract each other to live together. Early marriage is a marriage below the age limit stipulated by law, namely the age of 19 for men and women. The purpose of this study was to analyze the factors that influence early age marriage in Sidodamai Village, Samarinda Ilir District.This type of research is qualitative research with descriptive methods through interviews, observation, and documentation in data collection. The research subjects were 5 perpetrators of early marriage, 3 parents of early marriage actors, and 1 head of KUA Samarinda Ilir.The analysis shows that the factors that influence the high incidence of early marriage are the low level of parents' income and the level of education. The thing that most influences early marriage is pregnancy outside of marriage.It is advisable for the perpetrators of early marriages to prepare physically and mentally before the marriage takes place. In addition, parents of early marriage actors should not marry off their children at an early age, they should provide provisions for improving the quality and knowledge and understanding of their children in living life.